2021
DOI: 10.3389/fnins.2021.682126
|View full text |Cite
|
Sign up to set email alerts
|

MRI DTI and PDFF as Biomarkers for Lower Motor Neuron Degeneration in ALS

Abstract: ObjectiveTo evaluate the utility of nerve magnetic resonance imaging (MRI), diffusion tensor imaging (DTI), and muscle MRI multi-echo Dixon for assessing lower motor neuron (LMN) degeneration in amyotrophic lateral sclerosis (ALS).MethodsIn this prospective observational cohort study, 14 patients with ALS and 13 healthy controls underwent a multiparametric MRI protocol, including DTI of the sciatic nerve and assessment of muscle proton density fat fraction of the biceps femoris and the quadriceps femoris muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Previous studies on peripheral nerve repair have shown that the density and integrity of myelin increase during the process of nerve fiber regeneration, thereby resulting in higher FA and lower RD values ( Chen et al, 2017 ; Farinas et al, 2020 ; Zheng et al, 2021 ). Conversely, nerve anisotropy (FA) values decrease, and RD values increase during peripheral nerve degeneration in healthy older individuals or individuals with peripheral nerve disease because of decreased number of myelinated fibers ( Jeon et al, 2018 ; Lichtenstein et al, 2021 ). Therefore, FA and RD values are sensitive biomarkers to detect minor changes in the myelination of the peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on peripheral nerve repair have shown that the density and integrity of myelin increase during the process of nerve fiber regeneration, thereby resulting in higher FA and lower RD values ( Chen et al, 2017 ; Farinas et al, 2020 ; Zheng et al, 2021 ). Conversely, nerve anisotropy (FA) values decrease, and RD values increase during peripheral nerve degeneration in healthy older individuals or individuals with peripheral nerve disease because of decreased number of myelinated fibers ( Jeon et al, 2018 ; Lichtenstein et al, 2021 ). Therefore, FA and RD values are sensitive biomarkers to detect minor changes in the myelination of the peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on peripheral nerve repair have shown that the density and integrity of myelin increase during the process of nerve fiber regeneration, thereby resulting in higher FA and lower RD values (Chen et al, 2017;Farinas et al, 2020;Zheng et al, 2021). Conversely, nerve anisotropy (FA) values decrease, and RD values increase during peripheral nerve degeneration in healthy older individuals or individuals with peripheral nerve disease because of decreased number of myelinated fibers Lichtenstein et al, 2021). Therefore, FA and RD values are sensitive biomarkers to detect minor changes in the myelination of the peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI protocol was based on a protocol already established in studies of patients with chronic inflammatory demyelinating polyneuropathy or amyotrophic lateral sclerosis [ 14 , 19 ]. The well-established protocol was extended by a quantitative T2 mapping sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle MRI can be supplemented by nerve diffusion tensor imaging (DTI), revealing information about nerve damage and regeneration [14][15][16][17][18]. Previous studies in other neuromuscular and neuropathy disorders found a decreased fractional anisotropy (FA) in the sciatic nerve compared to controls [14,19]. So far, studies in SMA patients only investigated the FA in muscle tissue showing increased values compared to healthy controls but did not investigate nerve structures themselves [9,20].…”
Section: Introductionmentioning
confidence: 99%